The French Productivity Puzzle - Philippe Askenazy; Christine Erhel (Institute for the Study of Labor (IZA), 2015)
Since 2008, France experiences a sharp productivity slowdown. Both output per hour and total factor productivity are particularly deceptive in the market economy. This recent trend contrasts with the acceleration of productivity during the previous crisis in the 1990's and the continuous increase during the following decade. This text provides the first comprehensive exploration of this puzzling break. The direct impacts of the Great Recession on industry composition or reallocation of capital are not significant suspects for a slowdown occurring across business activities. Labour market mechanisms are better candidates. On the one hand, the French labour market policy has massively boosted the creation of low-productive jobs including very-short term employees and self-employed workers. On the other hand, firms, which benefit from massive tax cuts, have hoarded their high-skilled workforce. In addition, the spread of innovative HRM incentives, e.g. employee shareholding, seems to have turned productivity more sensitive to the business cycle (and especially to the fall of stock markets).
Keywords: O40; J20; D20; E24; 330; productivity slowdown; France; labour market policies; recession